On-body antenna wit parasitic elements - Kamarudin, Muhammad Ramlee (Penerbit UTM, 2008)
An antenna with multi-elements that act together to form an array is required to increase the gain. One example is the well-known Yagi-Uda antenna. Such an antenna is widely used for television communication in which it operates at high frequency (HF), very high frequency (VHF) and ultra high frequency (UHF). It consists of a driven element and a number of parasitic radiators in which currents are induced by mutual coupling. Some applications consider the mutual coupling effect undesirable because it degrades the performance. However, in the parasiticaray it is central to the operation. The parasite elements are useful to increase the gain, create a directional beam and enhance the bandwidth impedance of the antenna.